Development of a Group Guidance Model Based on Muhammadiyah Educational Values to Enhance Awareness of Bullying Behavior among Muhammadiyah Enrekang Students - Muliyadi, Muliyadi; Pandang, Abdullah; Sinring, Abdullah (Edumaspul: Jurnal Pendidikan, 2026)
Sustainable agriculture in Bali emerges from a harmonious integration of cultural values, spirituality, and local wisdom inherited across generations. Yet, increasing pressures from climate change and the demand for higher agricultural productivity raise a crucial question: how can these traditional values be integrated with global sustainability principles that emphasize resource efficiency, environmental stewardship, and food security? This becomes particularly relevant as key elements of sustainable agriculture such as soil and water conservation, responsible input use, crop diversification, and ecosystem preservation must be interpreted within Bali’s culturally embedded agricultural system. This study aims to describe sustainable agricultural practices in Subak Karangasem, Noongan Village, Karangasem Regency, by examining the role of traditional values and the Tumpek Uduh ritual in maintaining ecological, social, and spiritual balance. Using a descriptive qualitative approach with a case study design, data were collected through in depth interviews, field observations, and visual documentation involving three key informants. The findings show that despite a commodity shift from rice to horticultural crops such as chili and tomatoes, farmers in Subak Karangasem continue to uphold the principles of Tri Hita Karana as the philosophical foundation of their agricultural activities. The Tumpek Uduh ritual serves as a symbolic reinforcement of gratitude and respect for nature, reflecting the belief that plants and the environment are integral components of the ecological system that must be protected. Furthermore, the subak system functions not only as a water management institution but also as a sociocultural structure that strengthens community participation and mutual cooperation. This study concludes that sustainable agriculture in Bali is supported not only by technological adaptation but, more importantly, by local wisdom that maintains harmony between humans, nature, and God.